Abdullah bin Khamis, prose | عبدالله بن خميس ناثرا - Al Samhari | السمهري, Haya Bent Abd Arrahman | هيا بنت عبدالرحمن (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
This study dealt with the prose literature of the great Saudi writer Sheikh Abdullah bin Muhammad bin Khamis, a writer who has a prominent presence in the Saudi cultural scene. He is a poet, researcher, writer, investigator, journalist, and traveler. His cultural contributions had a strong influence on the paths of contemporary literature in the Kingdom of Saudi Arabia. When we talk about the writer Al-Khamis; We are talking about the science of smell, with diverse talents and encyclopedic knowledge, and this encyclopedism makes people of the arts fight to monopolize its lineage. The people of literature are well-versed and skilled among them, the people of geography are among them among the clever ones, and the people of history see him as the pillar of a tent with fixed tents. | تناولت هذه الدراسة الأدب النثري للأديب السعودي الكبير الشيخ عبد الله ابن محمد بن خميس ،وهو أديب له وجوده البارز في المشهد الثقافي السعودي، فهو شاعر، وباحث، وأديب، ومحقق، وصحفي، ورحالة. وقد كانت إسهاماته الثقافية ذات تأثير قوي في مسارات الأدب المعاصر في المملكة العربية السعودية.فحين نتحدث عن الأديب الخميس؛ فإنما نتحدث عن علَم أشم متنوع المواهب، موسوعي المعرفة، وهذه الموسوعية تجعل أهل الفنون يتنازعون للاستئثار بنسبته إليهم؛ فأهل الأدب هو الضليع المتمكن فيهم، وأهل الجغرافيا عد ٍ وه فيهم من الحاذقين، وأهل التاريخ رأوه عمود خيمة ثابتة الأطناب.